LEADERSHIP SKILLS IN ORDER TO INCREASE EMPLOYEE EFFEICIENCY - Nedovic, Mirjana; Sudaric, Zeljko; Ivankovic, Darija (European Scientific Journal, ESJ, 2014)
The role of leadership as a core management function becomes extremely important in the case of rapid changes occurring in the market, and then within an organization that must adapt to new changes. Therefore, management becomes a central topic of study within the field of management. Terms of managers and leaders are not equal, and have not same meaning. The manager may be the person who operates in a stable business environment; a leader is needed in terms of uncertainty that identifies new opportunities for the company in a dynamic business environment. Therefore, leadership, charisma and inspiring employees, and the use of power, are becoming the key to the success of the enterprise market, and among its competitors. There is no dilemma that is leadership crucial for its success or not, the importance of leadership is unquestioned. Therefore the study of this area management as a management tool is importance for the success of the business. A leadership skill derives satisfaction of employees work activity. The company, which have no leader will result , with bad results, not motivated and disgruntled employees, while the opposite, organization that are based on knowledge and expertise in the field of management will be successful in their own business domain. Because of its importance in achieving the goals set out by managers and organizations, purpose of this paper is to examine the effects of a valid, leadership on the effectiveness of employees in the enterprises. The results show that a leadership skill affects the efficiency of enterprises and employee motivation. Leadership skills becoming a key success factor in business and in achieving the organization’s objectives.